Highly sensitive acetone sensor based on Eu-doped SnO2 electrospun nanofibers. Issue 14 (1st November 2016) - Jiang, Ziqiao; Zhao, Rui; Sun, Bolun; Nie, Guangdi; Ji, He; Lei, Junyu; Wang, Ce
Abstract: In this study, a series of undoped and Eu-doped SnO2 nanofibers were synthesized via a simple electrospinning technique and subsequent calcination treatment. Field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were carefully used to characterize the morphologies, structures and chemical compositions of these samples. The results reveal that the as-prepared nanofibers are composed of crystallite grains with an average size of about 10 nm and Eu 3+ ions are successfully doped into the SnO2 lattice. Compared with pure SnO2 nanofibers, Eu-doped SnO2 nanofibers demonstrate significantly enhanced sensing characteristics (e.g., large response value, short response/recovery time and outstanding selectivity) toward acetone vapor, especially, the optimal sensor based on 2 mol% Eu-doped SnO2 nanofibers shows the highest response (32.2 for 100 ppm), which is two times higher than that of the pure SnO2 sensor at an operating temperature of 280 °C. In addition, the sensor exhibits a good sensitivity to acetone in sub-ppm concentrations and the detection limit could extend down to 0.3 ppm, making it a potential candidate for the breath diagnosis of diabetes.